A Comprehensive Assessment and Comparative Analysis of Simulations Tools for Cloud Computing (International Journal of Engineering and Computer Science, 2016)
Offering “Computing as a utility” on pay per use plan, Cloud computing has emerged as a technology of ease and flexibility for thousands of users over last few years. In Cloud, computational resources are rented avoiding huge investment on the industry part. Due to this attractive offering, adoption and deployment of Cloud have become very popular not only among industries but also in the research community. But, due to lack of infrastructure and due to problems using the real hardware and software resources because of its high costs and other economical issues, it is not always possible for the research community to work on the actual Cloud for carrying out their experiments and testing & implementing proposals. For fulfilling such requirement, modeling and simulation technologies are required which make them available a look and feel of real Cloud offerings. In this paper, we make an exhaustive assessment and comparative analysis of around twenty simulation tools for Cloud environment.